The Study of Profitability of Drugstores in Iran’s Pharmaceutical System: Profitability of drugstores in Iran - Mehdi Mohammadzadeh, (Iranian Journal of Pharmaceutical Sciences, 2010)
Pharmacy as the last unit in the pharmaceutical supply chain is responsible for supplying and dispensing medicines to the patients and giving required advices to them, based on their needs and physician’s prescriptions according to standard protocols of the country. Beside this responsibility, which is primarily on drugstores, this unit is regarded as a small business unit and should have economical feasibility and acceptable profit, so that it’s main responsibility will not be negatively affected by unfavorable economic situation. In this study, the profitability of pharmacies, in case they merely supply medicine and work out no other business, has been put into consideration. To carry out the research, case studies and interviews along with archival reviews and historical records have been used and income statement of case pharmacies has been inspected. The results show that in the case that Iranian pharmacies simply supply medicines, they will be loss-baring and to improve them and increase their outcome some measures need to be taken. Some recommendations have been offered in the discussion and conclusion section of this paper.